(untitled) (Communications in Computational Chemistry, 2025)
Electrochemical nitrogen oxide reduction reaction (NORR) can simultaneously remove atmospheric pollutant NO and produce the important chemical ammonia (NH_3), which, therefore, has garnered significant attention. However, the effect of molecule coverage on the catalyst surface on electrocatalytic activity is less discussed. In combination with atomic ab initio thermodynamics and first-principles calculations, the relationship between the NO coverage and catalytic NORR activity on Cu(111) is unraveled in this work. Results indicate that the adsorption stability and the limiting potential (U_L) of NORR on Cu(111) is closely related to NO coverage. In the case of standard conditions (1 atm, 300 K), NO adsorption with a coverage of 1/4 monolayer (ML) is the most stable configuration, though the corresponding U_L (0.34 V) is higher than those of 1/9 (0.29 V) and 1/16 ML (0.29 V) adsorption while significantly lower than that of 1 ML (0.78 V). Therefore, our study provides insights into the role of temperature, pressure, and molecule coverage in electrochemical reactions.